Pencemaran Nama Baik Melalui Fitnah dan Implikasinya terhadap Reputasi Individu (Studi Putusan Nomor 613/Pid.B/2020/Pn Stb) - Zulkifli, Suhaila; Rajagukguk, Nelson Wesly Bangun; Noor, Tajudin (Universitas Medan Area, 2025)
This article aims to analyze the legal regulations concerning defamation within the Indonesian legal system and to evaluate the judicial considerations in Decision Number 613/Pid.B/2020/PN Stb. The focus is on how positive law responds to defamation cases embedded in local social and cultural values. This study applies theories from classical and progressive criminal law. Data were collected through document analysis and library research, and examined using a normative juridical approach. The study concludes that defamation is comprehensively regulated under the Indonesian Penal Code (KUHP), the Electronic Information and Transactions Law (ITE Law), and the 1945 Constitution, though its application should account for societal context. The court’s decision reflects sensitivity to the local social structure and emphasizes the need for a balance between protecting individual reputation and ensuring freedom of expression. The article recommends a more restorative legal approach to support social reconciliation alongside the imposition of criminal sanctions.